The view to nationalism – terminological issues and the evolution of the concept - Meller, Arkadiusz (Social Development and Security, 2020)
Nationalism is one of those social phenomena that causes a series of doubts and misunderstandings. He is often accused of all evil, led by responsibility for carrying out ethnic cleansing. At the same time, there is no consensus among researchers about the importance of the main features that determine nationalism. Faced with the problem of determining what nationalism is, we often come across antinomic statements from one another. In view of this state of affairs, the question arises whether there is only one universally applicable type of nationalism, or whether it would be more appropriate to assert that there are many nationalist sentiments. The purpose of the article below is to try to discuss various opposing approaches to nationalism, to trace its evolution and find the answer to the question, can nationalism, as some authors want, be defined as a form of ideology?